Szacowanie kapitału ekonomicznego w ocenie niewypłacalności banków w Polsce - Krysiak, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper present option model applied for economic capital assessment for banks in Poland. Calculations were performed based on data drawn from banks quoted on Warsaw Stock Exchange. Current adequacy ratio for all banks exceed by far the required regulatory level. The results indicate that after applying option model which considers all type of risk assumed by bank, the total capital is going to be increased by 50% in relation to current level. Facing a lot of problems in the process of application of internal models at banks in Poland for credit, market and operational risk evaluation, presented methodology seems to be a promising tools to support realization of Basel II directives. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 296-308